Far-field optical nanoscopy with reduced number of state transition cycles - Staudt, Thorsten; Engler, Andreas; Rittweger, Eva; Harke, Benjamin; Engelhardt, Johann; Hell, Stefan (Optics express, 2011)
We report on a method to reduce the number of state transition cycles that a molecule undergoes in far-field optical nanoscopy of the RESOLFT type, i.e. concepts relying on saturable (fluorescence) state transitions induced by a spatially modulated light pattern. The method is exemplified for stimulated emission depletion (STED) microscopy which uses stimulated emission to transiently switch off the capability of fluorophores to fluoresce. By switching fluorophores off only if there is an adjacent fluorescent feature to be recorded, the method reduces the number of state transitions as well as the average time a dye is forced to reside in an off-state. Thus, the photobleaching of the sample is reduced, while resolution and recording speed are preserved. The power of the method is exemplified by imaging immunolabeled glial cells with up to 8-fold reduced photobleaching.
Gesehen am 21.10.2022